1989
DOI: 10.3758/bf03334654
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and insight in wolf (Canis lupus) and Alaskan malamute (Canis familiaris): Visual discrimination learning

Abstract: Hand-reared wolves performed better than Alaskan malamutes and maternally reared wolves on Wisconsin General Test Apparatus (WGTA) measures of oddity learning. Differences between the two groups of wolves are interpreted as motivational. Differences between the hand-reared wolves and the malamutes contradicted predictions that dogs should perform better than wolves on training tasks and suggested that the WGTA tasks are amenable to either trial-and-error ("associative") solutions typical of training-task perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 7 publications
(8 reference statements)
1
37
0
Order By: Relevance
“…It has been known for long that wolves can only be socialized if they are separated before eye opening from the mother (Klinghammer and Goodmann 1987) and they are raised separated from other wolves (and dogs) for the Wrst few months after birth. Frank et al (1989) reported that their wolf puppies that were fostered both by a wolf and humans and received less than 20 h of daily contact with humans were nearly as wary of humans as were pups reared without human contact. This means that wolves having received less extensive human contact and having been exposed too early to conspeciWcs (even if they tolerate the presence of humans) cannot be regarded as having comparable experience and being in the same arousal and motivational state as dogs when tested in such experimental situations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been known for long that wolves can only be socialized if they are separated before eye opening from the mother (Klinghammer and Goodmann 1987) and they are raised separated from other wolves (and dogs) for the Wrst few months after birth. Frank et al (1989) reported that their wolf puppies that were fostered both by a wolf and humans and received less than 20 h of daily contact with humans were nearly as wary of humans as were pups reared without human contact. This means that wolves having received less extensive human contact and having been exposed too early to conspeciWcs (even if they tolerate the presence of humans) cannot be regarded as having comparable experience and being in the same arousal and motivational state as dogs when tested in such experimental situations.…”
Section: Discussionmentioning
confidence: 99%
“…Frank and Frank (1982) socialized four wolves and four dog puppies (malamutes) in parallel both to humans and wolves/dogs, and in a replication study hand-reared seven wolf pups with higher exposure to people and contact with only littermates. These animals have been tested in various tasks involving visual discrimination learning (Frank et al 1989), problem solving (Frank and Frank 1982) and training tasks (Frank and Frank 1987). More recently, there have been two studies comparing dogs' and wolves' use of human-given cues to Wnd hidden food in object-choice tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feddersen-Petersen (1986) compared the intraspecific behavior of young wolves and dogs having limited contact with humans. Others have raised wolves and dogs in human environments (Fentress, 1967;Frank, 1980;Frank & Frank, 1982a;Frank, Frank, Hasselbach, & Littleton, 1989;Woolpy & Ginsburg, 1967) in order to investigate motivational and cognitive differences. Such comparative research usually assumes that the revealed species characteristics and/or specific differences reflect the influences of differential genetic determination.…”
Section: Introductionmentioning
confidence: 99%